Interdependent intercultural task as a tool for developing intercultural awareness through Collaborative Online International Learning in Global Leadership - Lori M. Curtindale; Svetlana G. Krylova; Svetlana A. Minyurova (University of Groningen Press, 2020)
This paper discusses a teaching approach that can be used in Collaborative Online International Learning - Interdependent Intercultural Tasks (IIT). IIT are characterized by the following features: (1) they include culture-specific information that creates cognitive dissonance and motivates students to analyze information about another culture; (2) they provide instructions aimed at learning subjective information about individuals from another culture; and (3) they can only be performed through interaction between students from different countries. We expect two learning outcomes of implementing IIT in a Global Leadership course; an increase in (1) intercultural interaction when working on a collaborative project; and (2) awareness of general cultural differences and those related to a specific global problem. Preliminary findings suggest that employing IIT (i.e. having students discuss native and non-native country media articles describing culture-specific perspectives on a global problem) increases the frequency of student interactions outside the classroom and improves coordination between teammates.